Предмет: Алгебра,
автор: BebopVox777
Выразить переменную X из формулы:
a * b * (x - c) = d * e * (x - f)
Ответы
Автор ответа:
0
a * b * (x - c) = d * e * (x - f)
abx-abc=dex-def
abx-dex=abc-def
x(ab-de)=abc-def
x=(abc-def)/(ab-de)
abx-abc=dex-def
abx-dex=abc-def
x(ab-de)=abc-def
x=(abc-def)/(ab-de)
Похожие вопросы
Предмет: Математика,
автор: kotajanastasya
Предмет: Обществознание,
автор: porsche94
Предмет: Английский язык,
автор: sashatkachuk852
Предмет: Литература,
автор: Plotitsynaa
Предмет: Математика,
автор: Lil11111111